Advanced gastric cancer with metachronous intracranial oligometastases without recurrence after multidisciplinary team discussion and comprehensive treatment: a case report - Shao, Lijuan; Zhang, Hongyu; He, Wenting; Wu, Jun; Zhu, Danxia; Cheng, Haibo (Frontiers in Oncology, 2023)
This article describes the process of multidisciplinary team (MDT) discussion and comprehensive treatment of a case of advanced gastric cancer that tested positive for programmed death ligand 1 (PD-L1). During diagnosis, the patient presented with advanced gastric cancer and numerous unresectable metastases in the lesser omental lymph nodes, both lungs, liver, and left parietal occipital lobe. A meeting was arranged for the departments of oncology, gastrointestinal surgery, radiotherapy, imaging, and pathology to discuss the case. Initially, the patient had a partial response to the first-line treatment, which was a combination of pembrolizumab and chemotherapy. However, after nineteen months, the patient presented with a metachronous isolated lesion in the left frontal lobe. After mutual agreement among the oncology, brain surgery, gastrointestinal surgery, radiotherapy, imaging, and pathology departments, the intracranial lesion underwent resection. Following this, the operation was supplemented by stereotactic radiation therapy (SRT) and whole-brain radiation therapy (WBRT). The patient showed excellent signs of recovery after the operation, and her general condition remained favorable after 16 months of follow-up. Nonetheless, the outlook for patients facing advanced-stage gastric cancer remains distressing. Through multidisciplinary team (MDT) discussions, patients diagnosed with advanced gastric cancer can receive standardized diagnostic and treatment approaches to develop reasonable and personalized comprehensive treatment plans. Such plans help to improve the quality of life of patients and effectively prolong their survival time.